Evolution of Religion in Mass Consciousness - Zasimauskas, Leonardas (Problemos, 1983)
The study of the evolution of religion in mass consciousness requires, according to the author, the finding out of two interrelated points: firstly, the explanation of the process of succession of religious ideas and, secondly, the analysis of reasons in the crisis of the above ideas, i.e., atheisation of mass consciousness. The author grounds the thesis that the evolution of religion in mass consciousness is a complex, many-sided process, closely linked with the development of such cultural phenomena as science, morals, philosophy, art, at the same time being interlaced with the conflicting development of social context.